Statistical optimization of process conditions for disinfection of water using defatted moringa oleifera seed extract - Muyibi, Suleyman Aremu; Idris Oseni, Munirat; Jami, Mohammed Saedi; Jamal, Parveen; Abdul Karim, Mohamed Ismail (World Academy of Science, Engineering and Technology (W A S E T), 2013)
In this study, statistical optimization design was used to study the optimum disinfection parameters using defatted crude Moringa oleifera seed extracts against Escherichia coli (E. coli) bacterial cells. The classical one-factor-at-a-time (OFAT) and response surface methodology (RSM) was used. The possible optimum range of dosage, contact time and mixing rate from the OFAT study were 25mg/l to 200mg/l, 30minutes to 240 minutes and 100rpm to 160rpm respectively. Analysis of variance (ANOVA) of the statistical optimization using faced centered central composite design showed that dosage, contact time and mixing rate were highly significant. The optimum disinfection range was 125mg/l, at contact time of 30 minutes with mixing rate of 120rpm.